(untitled) (American Journal of Islam and Society, 2016)
The Summer Institute for Scholars 2016, held at the IIIT headquarters in Herndon, VA, from August 8-13, 2016, brought together a group of scholars to address “Islamic Thought and Secular Modernity.” In order to present as many of their ideas as possible, the wide-ranging and thought-provoking comments of the chairs and the discussants are not recounted here.